ANALYSIS OF SPEECH ACTS IN SUSILO BAMBANG YUDHOYONO’S POLITICAL SPEECH - Tesa Jatnika Permana; Arham Mauriyat (PROJECT (Professional Journal of English Education), 2021)
Speech acts are utterances which do not only have explicit meaning but also implicit meaning. Political speech acts are such an important issue for politicians as they can provide information to regulate people's thoughts and opinions through political language which is used as the main key. This research examined speech acts’ implementation in political speech, including the types of speech acts by politicians in political speech as well as their functions, in order to give a theoretical analysis about every utterance in political speech through context of meaning. The data were analyzed qualitatively where the researchers describe the results in the form of words and explanations by adopting Searle’s theory. It was found that the types of speech acts that mostly appeared in Susilo Bambang Yudhoyono’s political speech are nine assertives, eight commissives and four directives. Each type of the speech acts delivered a different context of meaning. Keywords:  Speech Acts, Political Speech, Illocutionary